The murine choline-deficient, ethionine-supplemented (CDE) diet model of chronic liver injury - Gogoi-Tiwari, J.; Köhn-Gaone, J.; Giles, C.; Schmidt-Arras, D.; Gratte, F.; Elsegood, Caryn; McCaughan, G.; Ramm, G.; Olynyk, John; Tirnitz-Parker, Nina (Journal of Visualized Experiments, 2017)
Chronic liver diseases, such as viral hepatitis, alcoholic liver disease, or non-alcoholic fatty liver disease, are characterized by continual inflammation, progressive destruction and regeneration of the hepatic parenchyma, liver progenitor cell proliferation, and fibrosis. The end-stage of every chronic liver disease is cirrhosis, a major risk factor for the development of hepatocellular carcinoma. To study processes regulating disease initiation, establishment, and progression, several animal models are used in laboratories. Here we describe a six-week time course of the choline-deficient and ethionine-supplemented (CDE) mouse model, which involves feeding six-week old male C57BL/6J mice with choline-deficient chow and 0.15% DL-ethionine-supplemented drinking water. Monitoring of animal health and a typical body weight loss curve are explained. The protocol demonstrates the gross examination of a CDE-treated liver and blood collection by cardiac puncture for subsequent serum analyses. Next, the liver perfusion technique and collection of different hepatic lobes for standard evaluations are shown, including liver histology assessments by hematoxylin and eosin or Sirius Red stainings, immunofluorescent detection of hepatic cell populations as well as transcriptome profiling of the liver microenvironment. This mouse model is suitable for studying inflammatory, fibrogenic, and liver progenitor cell dynamics induced through chronic liver disease and can be used to test potential therapeutic agents that may modulate these processes.